2022
DOI: 10.3390/ijms23179640
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Gold Nanoparticles and Alpha-Lipoic Acid Mixture against Radiation-Induced Brain Damage in Rats

Abstract: The current study aims to evaluate the possible neuroprotective impact of gold nanoparticles (AuNPs) and an alpha-lipoic acid (ALA) mixture against brain damage in irradiated rats. AuNPs were synthesized and characterized using different techniques. Then, a preliminary investigation was carried out to determine the neuroprotective dose of AuNPs, where three single doses (500, 1000, and 1500 µg/kg) were orally administrated to male Wistar rats, one hour before being exposed to a single dose of 7Gy gamma radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…1(E). It showed that the peaks at 3416 cm − 1 , 1621 cm − 1 and 623 cm − 1 corresponding to bonded amide (-NH-) stretching vibrations, which further approving the effective conjugation of PEGylated-Au@ALA NPs surface [27].…”
Section: Characterization Of Au@ala Npsmentioning
confidence: 87%
“…1(E). It showed that the peaks at 3416 cm − 1 , 1621 cm − 1 and 623 cm − 1 corresponding to bonded amide (-NH-) stretching vibrations, which further approving the effective conjugation of PEGylated-Au@ALA NPs surface [27].…”
Section: Characterization Of Au@ala Npsmentioning
confidence: 87%
“…The mixture of α-lipoic acid with gold nanoparticles showed a superior neuroprotective effect compared to each compound alone in vivo, with the inhibition of brain damage induced by radiation in rats [ 157 ]. The combination of α-lipoic acid with PEGylated gold nanoparticles proved to counteract oxidative stress in osteoporosis development.…”
Section: Exploring the Role Of α-Lipoic Acid In Therapeutic Nanoplatf...mentioning
confidence: 99%
“…The following peaks were identified, with position 2θ = 38.1 • , 44.4 • , 64.9 • , and 77.5 • , corresponding to a planar interspacing of 0.235, 0.204. 0.144, and 0.123 nm, respectively, and can be assigned to the planes (111), ( 200), (220), and (311) of the FCC gold structure [22,47].…”
Section: X-ray Powder Diffraction (Xrd)mentioning
confidence: 99%